Simultaneous Electrochemical Detection of Dopamine, Ascorbic Acid and Uric Acid Using Copper-Phthalocyanine Functionalized Mwcnts - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J (Sociedad Chilena de Quimica, 2013)
Multiwalled carbon nanotububes functionalized with amino groups (MWCNT-NH2) and further modified with copper- phthalocyaninetetrasulphonate (4?(SO3) CuPc) were used for preparing a hybrid electrode [MWCNT-NH2/4?(SO3)CuPc/GC] using glassy carbon (GC) as a support. This hybrid electrode was tested for the detection of dopamine (DA) in the presence of ascorbic acid (AA) and uric acid (UA) in a PBS buffer solution at pH 6.8. The presence of the macrocyclic increased the resolution of the oxidation signals of AA, DA and UA into three very well distinct oxidation peaks. This effect was enhanced when the complex is adsorbed on multiwalled carbon nanotubes. In addition, the hybrid films provide a simple method for selective detection of DA, AA and UA in biological samples. The calibration curves for DA were obtained over the range of 1x10-6-1x10 -3M, obtaining a good selectivity and sensitivity.